Finno-Ugric Rune Song Tradition Revisited: A Critical Discourse Analysis of Värttinä's "Äijö" - Heinonen, Yrjö (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2005)
Contemporary Finnish folk music, unlike internationally successful contemporary Finnish rock (HIM, Nightwish, The Rasmus), transmits Finnish and Finno-Ugric tradition in a reinterpreted form to international audiences. This article explores this transmission through a case analysis of Äijö, a song by Värttinä, "the brand name" of Finnish World Music. Critical Discourse Analysis (CDA) provides a unified framework, which allows for tan examination of how different folk music traditions and the practices of Western popular music have been used in Äijö. The data with which this research was undertaken consists of publicly available media texts representing different stages of the production, distribution and consumption of Äijö.